RETRACTED ARTICLE: Effectiveness of Social Media Platforms in Disseminating Qur'anic Teachings among Contemporary Muslims - Sule, Muhammad Maga; Mainiyo, Attahir Shehu (Alhadharah: Jurnal Ilmu Dakwah, 2023)
Retraction Notice This article has been retracted from Alhadharah: Jurnal Ilmu Dakwah because the authors submitted the same work to multiple journals, resulting in duplicate publication. The article was first published in Spektra: Jurnal Ilmu-ilmu Sosial, Vol. 5 No. 1 (2023), pp. 47-64, on 22 September 2023, with the same title: "EFFECTIVENESS OF SOCIAL MEDIA PLATFORMS IN DISSEMINATING QUR’ANIC TEACHINGS AMONG CONTEMPORARY MUSLIMS". Authors are explicitly informed before submission that the manuscript must not have been previously published or be under consideration for publication elsewhere. Submitting the same research to more than one journal without appropriate acknowledgment constitutes a breach of publication ethics. The article has been retracted in accordance with the Committee on Publication Ethics (COPE) guidelines, following a recommendation by the editors after consultation with other members of the editorial team. We apologise to the readers, reviewers, and editorial boards of both journals for this breach of ethical standards. The editorial team of Alhadharah: Jurnal Ilmu Dakwah will take necessary measures to prevent similar incidents in the future.